Otokritik terhadap Kemandirian Badan Peradilan dalam Undang Undang Dasar Negara Republik Indonesia Tahun 1945 - Kamaruddin Kamaruddin (Justicia Islamica, 2014)
The independence of judicial bodies is the freedom to run and administer justice without interference from various parties, both judicial and executive interventions in upholding law and justice. Specifically regulated in Law No. 48 of 2009 concerning Judicial Power. Article 1 paragraph (1) states that “Judicial power is an independent state power to administer justice in order to uphold law and justice based on Pancasila and the 1945 Constitution of the Republic of Indonesia, for the implementation of the rule of law of the Republic of Indonesia.” Independent judicial power must be upheld both as a principle in a state based on law and to enable judicial power to ensure that government is not carried out arbitrarily or oppressively. Therefore, in order to realize a complete/kaffah independence of the judiciary, it is necessary to have a legal system that is always inspired by the value of divinity (Islam), so that the judicial independence of the judiciary under the Supreme Court is independent and free from the influence of the intervention of government power or other powers.